The Impact of Initial Symptom on the Timing of Diagnosis and Clinical Course of Osteosarcoma - Karaismailoğlu, Bedri; Özşahin, Mahmut Kürşat; Görgün, Barış; Hız, Veli Muzaffer Murad (Cerrahpaşa Medical Journal, 2023)
Objective: This study aimed to analyze the attitude of patients and health care providers regarding the initial symptoms of osteosarcoma and the effect of their attitude on the timing of diagnosis and clinical course. Methods: The osteosarcoma patients who were referred to our clinic between 1995 and 2015 were reviewed retrospectively. The patients were grouped according to their initial symptoms as “pain without swelling,” “swelling without pain,” or “pain with swelling.” The delayed referral and delayed diagnosis durations were noted. The relationship between the type of initial symptom and delays in referral or diagnosis was analyzed. The effect of delays on the prognosis of osteosarcoma was investigated. Results: One hundred eighty-five patients were available for the final analysis. The median age was 21 (12-69). The pain without swelling group had significantly higher delayed referral (2.10 months) and delayed diagnosis (1.53 months) values compared to both swelling without pain (P = .031, .042) and pain with swelling groups (P = <.001, <.001). The swelling without pain group also showed higher delayed referral (1.30 months) and delayed diagnosis (1.01 months) compared to the pain with swelling group (P = .049, P = .004). No significant difference was found between the groups regarding the rates of metastasis at presentation, recurrence, and 5-year survival. Conclusion: The symptom of pain without swelling is more likely to be overlooked by patients, their parents, and doctors, compared to swelling with or without pain, and can cause a delay in the diagnosis of osteosarcoma. Cite this article as: Karaismailoğlu B, Kürşat Özşahin M, Görgün B, Muzaffer Murad Hız V. The impact of initial symptom on the timing of diagnosis and clinical course of osteosarcoma. Cerrahpaşa Med J. 2023;47(1):33-36.